Sistem Informasi Kependudukan (Studi Kasus: Desa Paya Bengkuang Kab. Langkat) - Tuti Awaliyah; Surizar Rahmi Danur; David JM. Sembiring; Sinek Mehuli Br PA (JISTI: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
Population Information System in terms of managing Population Data based on age classification. Paya Bengkuang Village currently has an information system that is still in manual form, which slows down the process of searching, adding, changing or deleting population data. Therefore, it is necessary to carry out research to build a population information system. The aim of this information system is to make it easier for village officials to manipulate population data and inform them in order to provide efficiency in community services. In this implementation, the PHP programming language is used and MySQL is used as the database. Based on the research results, it can be concluded that this website can be used to handle the process of filling in data, changing data, deleting and searching for population data, this system can also provide printed reports of certificates.